2020
DOI: 10.22478/ufpb.2317-6032.2020v24n2.48409
|View full text |Cite
|
Sign up to set email alerts
|

[Id 48409] Leishmaniose Tegumentar Americana E Leishmaniose Visceral: Perfil Epidemiológico Em Alagoas 2013- 2017

Abstract: Objetivo: Caracterizar o perfil epidemiológico dos casos de leishmaniose tegumentar americana e visceral em Alagoas, no período de 2013 a 2017. Metodologia: Estudo epidemiológico transversal de abordagem quantitativa, utilizando-se o coeficiente de incidência por 100 mil habitantes, razão de risco da ocorrência dos casos, tendência linear e a análise da relação dos casos ocorridos utilizando a correlação de Pearson. Os dados foram coletados do DATASUS e do IBGE. Resultados: Foi observado o registro de 331 caso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…According to the survey, the largest reported cases of ATL were in the rural area, aged between 20 and 30 years. Santos et al, 18 when carrying out an epidemiological study in the state of Alagoas, observed that 39% of cases were ATL, with a prevalence in people aged between 20 and 49 years, corroborating with those found in this research.…”
Section: Visceral Leishmaniasissupporting
confidence: 87%
See 2 more Smart Citations
“…According to the survey, the largest reported cases of ATL were in the rural area, aged between 20 and 30 years. Santos et al, 18 when carrying out an epidemiological study in the state of Alagoas, observed that 39% of cases were ATL, with a prevalence in people aged between 20 and 49 years, corroborating with those found in this research.…”
Section: Visceral Leishmaniasissupporting
confidence: 87%
“…It assumes that this high incidence is related to work activities carried out in regions, such as prospecting activities, agriculture, wood exploitation, agrarian settlements close to forest areas (large scale), deforestation for implementing pastures, in addition to the favorable climatic conditions for the vector development. 18 ATL has three transmission patterns: wild -anthropic actions bring man closer to the forest, habitat of wild animals; occupational -occurs in areas of exploitation of forests related to deforestation and construction; and rural or peri-urban -related to migratory areas and occupations in urban regions, close to secondary forests 19 , which refers to pattern transmission of the city of Cametá, since it presents characteristics of territorial expansion and similar socioeconomic activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A faixa etária média de casos analisados de leishmaniose visceral foi de 33,03 anos, um dos fatores que corroboram para esse resultado é a maior incidência de notificação entre homens, que em sua idade produtiva realizam principalmente atividades profissionais em ambientes suscetíveis a transmissão (15) . Além disso, esse acontecimento pode ser atribuído à coinfecção pelo HIV, uma vez que essa doença ocorre mais frequentemente na faixa etária de 18 a 50 anos (16) .…”
Section: Discussionunclassified